Challenging of Pesantren Students on Technology Era 4.0 - Mar'atus Sholehah (Universitas Darussalam Gontor, 2023)
This research investigated the Challenging of Pesantren Students on Technology Era 4.0. Technology from time to time is developing. It could be challenging for people, especially for students at Pesantren. They could not reach devices as they want. They lived in a place where conducted limited devices. The research purpose was used to answer the â€œHow are Pesantren students challenging technology 4.0?â€. It was conducted with a single case study. To collect the data, the researcher used setting or natural conditions, primary and secondary source data, and most data that got from observation, interviews, and documents. The steps of data collection are data reduction, data display, and conclusion drawing/verification. Trustworthiness was used in this study to make it reliable and valid. The researcher drew the conclusion based on the findings and discussions of the data; it can be concluded that there are two conclusions. First, technology era 4.0 for Pesantren students gave a positive effect. The discipline of the place where they live avoided the negative aspect of technology such as hoax news, and being a creative person because of the limitation of accessing the internet. They live in real life physically and psychologically. From a health aspect, they avoided radiation. Thus, they focused on their era now in a health condition. Second, technology era 4.0 for Pesantren students gave negative effects such as they only the users, not the developer or creators. The researcher hopes, that further researchers will be better, more complete, and more wonderful in their analysis of the media and social development aspect of the education section